2020
DOI: 10.1021/acs.macromol.0c00261
|View full text |Cite
|
Sign up to set email alerts
|

Functional Poly(ester-alt-sulfide)s Synthesized by Organo-Catalyzed Anionic Ring-Opening Alternating Copolymerization of Oxiranes and γ-Thiobutyrolactones

Abstract: The copolymerization of tert-butyl glycidyl ether (tBuGE), allyl glycidyl ether (AGE), ethoxyethyl glycidyl ether (EEGE) and 1,2-epoxybutane (BO) with γ-thiobutyrolactone was investigated using benzyl alcohol–phosphazene bases as initiating systems. The prepared copolymers display perfect (poly­(ester-alt-sulfide)) alternating structures for all epoxide monomers as evidenced by 1H, 13C, and 2D NMR and MALDI–TOF mass spectrometry. A marked influence of the reaction temperature on the occurrence of transesterifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…This phenomenon has been previously found for the alternating ring-opening copolymerization of thiolactone with epoxides and was explained by undesired chain transfer reactions to water molecules and by transesterification reaction between the propagating alcoholate species and the ester groups of the main chain. 34,35 In order to reduce the occurrence of side reactions, one solution is to add solvent and to decrease the reaction temperature. Thus, a NHTL-DEGE copolymerization with an identical reactant ratio was performed in THF at 55°C (Table 1, run 6).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been previously found for the alternating ring-opening copolymerization of thiolactone with epoxides and was explained by undesired chain transfer reactions to water molecules and by transesterification reaction between the propagating alcoholate species and the ester groups of the main chain. 34,35 In order to reduce the occurrence of side reactions, one solution is to add solvent and to decrease the reaction temperature. Thus, a NHTL-DEGE copolymerization with an identical reactant ratio was performed in THF at 55°C (Table 1, run 6).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that no homopolymerization of both monomers occurred using the same initiating system at 90°C and by analogy with the recently reported alternating AROP of γ-thiolactone with epoxides, perfectly alternating structures are postulated (Scheme 1). [29] Three experiments were performed at 90, 60 and 30°C (Table 1, runs 3, 7-8). An increase of the viscosity followed by a phase separation took place.…”
Section: ð (Sec) [°C] [H] [%] [G Molmentioning
confidence: 99%
“…A similar behavior was previously described for the alternating copolymerization of γ-butyrothiolactone with epoxides. [29] A higher amount of BEMP (2 eq., Table 1, run 5) resulted in even more reduced M n and higher Ð (Table 1, run 5). It was previously demonstrated that higher amount of phosphazene base favor the occurrence of side-reaction due to an increase the propagating center reactivities.…”
Section: ð (Sec) [°C] [H] [%] [G Molmentioning
confidence: 99%
See 2 more Smart Citations